Analysis of axial compression performance of steel - foamed ceramsite concrete composite structure wallboard. Issue 1 (1st June 2022) - Hong, Cheng; Tian, Zhixiang; Liu, Kai; Tu, Bin; Zhang, Tianlin
Abstract: Through the finite element analysis of the vertical axial load test of 9 self bearing and self insulation precast walls, the effects of the thickness of section steel, the strength of section steel, the strength of foamed ceramsite concrete, the layout of section steel and the thickness of foamed ceramsite plate on the failure mode, bearing capacity and overall stress of the wall plate are studied. The research shows that the strength of foamed ceramsite concrete is the main factor affecting the wall stress-strain curve, the layout form of section steel and wall thickness are important factors, and the change of section steel thickness and section steel strength has little effect on the stress-strain curve. The strength of foamed ceramsite concrete decreases by 30%, the wall bearing capacity decreases by 15%, and the wall deformation increases by three times. Therefore, quality management should be strengthened in the production process of foamed ceramsite concrete to prevent the strength decline of foamed ceramsite concrete due to production reasons; Foamed ceramsite concrete and section steel frame are constrained to form a stressed whole, and the ribbed section steel frame bears the main load, which provides a basis for subsequent experimental research and engineering design.